2011
DOI: 10.1186/1471-2458-11-808
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome is associated with change in subclinical arterial stiffness - A community-based Taichung Community Health Study

Abstract: BackgroundThe aim of this study was to evaluate the effect of MetS on arterial stiffness in a longitudinal study.MethodsBrachial-ankle pulse wave velocity (baPWV), a measurement interpreted as arterial stiffness, was measured in 1518 community-dwelling persons at baseline and re-examined within a mean follow-up period of 3 years. Multivariate linear regression with generalized estimating equations (GEE) were used to examine the longitudinal relationship between MetS and its individual components and baPWV, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 39 publications
3
20
1
4
Order By: Relevance
“…regression model (ENTER method). Elevated baPWV (1, no; 2, yes), determined according to the age-stratified and sex-stratified normal reference values, 12 and abnormalities of the MetS components (1, no; 2, yes) were used as dummy variables. Data were analyzed using the SPSS statistical software, version 17.0 (SPSS Inc, Chicago, IL), with the exception of the KruskalWallis test and the Dunn's post hoc analysis, which was performed using the GraphPad Prism software, version 5.0 (GraphPad Software Inc, San Diego, CA).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…regression model (ENTER method). Elevated baPWV (1, no; 2, yes), determined according to the age-stratified and sex-stratified normal reference values, 12 and abnormalities of the MetS components (1, no; 2, yes) were used as dummy variables. Data were analyzed using the SPSS statistical software, version 17.0 (SPSS Inc, Chicago, IL), with the exception of the KruskalWallis test and the Dunn's post hoc analysis, which was performed using the GraphPad Prism software, version 5.0 (GraphPad Software Inc, San Diego, CA).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that baPWV is greater in subjects with MetS than those without it. 11,12 In addition, the cardiovascular morbidity associated with MetS is greater in women than in men. It is likely that women with MetS develop greater atherosclerosis; however, this is not yet definitive.…”
mentioning
confidence: 99%
“…In both Western and Asian populations, cardiovascular morbidity and mortality is 2-5 times higher in those who are suffering from this syndrome than those who are not affected by MS [8]. The prevalence of MS has been reported in various countries differently.…”
Section: Introductionmentioning
confidence: 98%
“…It was found that subjects with MS had significantly greater baPWV at the endpoint than those without MS, after adjusting for age, gender, education, hypertension medication and mean arterial pressure. Arterial stiffness increased as the number of MS components increased[24]. Zhu et al enrolled a total of 5,476 subjects from annual health checkups and demonstrated that the values of baPWV and its change rates in MS patients were both higher than those in non-MS subjects.…”
Section: Discussionmentioning
confidence: 99%